The Diversity of Insect in Paddy Field in Karawang, West Java with Different Pest Management Techniques - Lutfi Afifah; Darso Sugiono (Institut Pertanian Bogor, 2020)
The practice of rice crop cultivation will affect the trophic structure and the diversity of insects that are formed. One of the common cultivation practices carried out by farmers was the control of pests by using pesticides. This study aimed to find out which pest management strategies that are effective in maintaining environmental health and understanding how natural enemies were affected by the application of synthetic pesticides. The first treatment was paddy field with integrated pest management (IPM), the second treatment was conventional rice field with a technique of chemical pest management (C-T), while the third treatment was mixed pest management (M-T). Insect sampling was conducted using sweep net, pitfall trap, and direct observation for 10 weeks after planting. Overall, it was found 100 morphospecies, 9 Orders, 56 families, with a total abundance of 6242 individuals per planting season. Based on functional roles it was found 39% as herbivores, 30% as predators, and 14% as parasitoids, 1% pollinators, and 13% decomposers. High insect diversity and abundance were found in the plots using low synthetic pesticides. The C-T control plot had a lower relative abundance of herbivorous insects, parasitoid insects, predators, and decomposers than the other control plots. H' and D index in the Integrated Pest Management (IPM) and Mixed Pest Management (M-T) plots did not show significant differences but differed significantly from the Chemical Control plot (C-T). Therefore, controlling the herbivore insects could apply the pest management based on IPM strategies. Keywords: Diversity of insects, integrated pest management (IPM), natural enemies, pesticides, rice pests